Global Mental Health and Pharmacology: The Case of Attention Deficit and Hyperactivity Disorders in Brazil - Ortega, Francisco; Müller, Manuela Rodrigues (Frontiers in Sociology, 2020)
Global Mental Health (GMH) is a field of teaching, research, and intervention with the goal of improving access to mental health worldwide. It is based on the global burden of disease research program and the existence of a large “treatment gap” between the need and availability of mental health services, with individual and social costs of undiagnosed and untreated mental disorders, especially in low- and middle-income countries (LMIC). Few academic publications in Brazil dialogue directly with the field of GMH, although several issues drawn from its agenda have been the subject of mental health policies in the country. Brazil can be classified as a middle-income country with a well-structured national health system. This system is oriented towards primary health care, which integrates both community mental health services and the broader health care network. The debate between GMH advocates and critics has unearthed old controversies in psychiatry such as universality or cultural specificity of mental disorders, their expressions, and its relationship with social and economic factors. We intend to examine how these controversies reverberate in Brazilian mental health, taking as an illustration the debates around Attention Deficit Hyperactivity Disorder (ADHD) in the country. ADHD discussions oppose those who argue that the condition is underdiagnosed and undertreated, and those who claim that there is overdiagnosis and overtreatment and thus, medicalization of childhood. This article presents the current status of the Brazilian mental health literature on ADHD, with emphasis on tensions around diagnosis, prevalence and interventions. Our aim is to highlight how the differential in discourse shapes the debate on ADHD in Brazil and how this can contribute to the GMH agenda. This goal will be undertaken in three steps. We will first briefly examine studies around GMH and ADHD. Secondly, we address Brazilian studies on this theme, considering the specificities of the constitution of the mental health field. Finally, we will examine the debate of treatment gap vs medicalization in the country in order to underscore the potentials and limitations of each perspective.